Prevalence of Congenital Hypothyroidism; in Rural Area of District Gautam Budha Nagar (U.P.) (Medico Legal Update, 2019)
Introduction:- Congenital hypothyroidism is a condition that affects the newborns and results from a partialor complete loss of thyroid function. Congenital hypothyroidism occurs when the thyroid gland fails todevelop the thyroid hormone or do not function properly. In 80 to 85 percent of cases, the thyroid gland isabsent, abnormally located, or severely reduced in size. In the remaining cases, a normal-sized or enlargedthyroid gland is present, but production of thyroid hormones is decreased or absent. If untreated, congenitalhypothyroidism can lead to intellectual disability and abnormal growth. Iodine is an essential dietary elementwhich is required for the synthesis of the thyroid hormones, thyroxine (T4) and tri-iodothyronine (T3). Inendemic goiter areas, congenital hypothyroidism may occur due to iodine deficiency.Aim:- To screen the Rural area’s neonates for Congenital Hypothyroidism.Results:- The prevalence of CH is 4/161 live birth observed in the rural area of Gautam Buddha NagarDistrict and it also observed that the mean level of TSH was higher in female compared to male neonates.Conclusion:- Despite the overwhelming evidence of a high prevalence of CH in India, this imminentlytreatable cause for developmental delay and mental retardation continues to await a credible universalscreening programme. To get the actual picture of CH in the study area is to need to screen more neonates,which helps to make the more precise evaluation of CH.